Evaluation of soil and groundwater remediation strategies for decommissioning nuclear facilities on the basis of sustainability assessment incorporating net present value - Jooste, Caroline S. (2016)
The decommissioning of nuclear facilities and remediation of radiological and non radiological contaminated land is currently being undertaken at some Magnox nuclear licensed sites in the UK. Sustainability needs to be considered so that well balanced remediation strategies are chosen that accommodate the long time frames decommissioning can take. Sustainable remediation options assessment involves selecting feasible soil and groundwater strategies to meet risk reduction goals whilst maximising the environmental, social and economic benefits.